An anti-CD45RO immunotoxin kills HIV-latently infected cells from individuals on HAART with little effect on CD8 memory - Saavedra-Lozano, J. (National Academy of Sciences, 2004)
CD4(+) CD45RO(+) T cells are the major latent viral reservoir in HIV-infected individuals and hence a major obstacle in curing the disease. An anti-CD45RO immunotoxin (IT) can decrease the number of both productively and latently infected CD4(+) T cells obtained from HIV-infected individuals with detectable viremia. In this study, we determined whether this IT could also kill latently infected replication-competent CD4(+) T cells obtained from infected individuals without detectable plasma viremia. Our results demonstrate that ex vivo treatment with the anti-CD45RO IT significantly reduced the frequency of these cells. In contrast, the IT had only a modest effect on the cytomegalalovirus-specific memory responses of CD8(+) T cells. These results suggest that purging latent cells from infected individuals on highly active antiretroviral therapy with the anti-CD45RO IT might reduce the HIV latent reservoir without seriously compromising CD8(+) T cell memory responses.